2016
DOI: 10.1016/j.ijpsycho.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory sinus arrhythmia reactivity to a sad film predicts depression symptom improvement and symptomatic trajectory

Abstract: Respiratory sinus arrhythmia (RSA) reactivity, an index of cardiac vagal tone, has been linked to self-regulation and the severity and course of depression (Rottenberg, 2007). Although initial data supports the proposition that RSA withdrawal during a sad film is a specific predictor of depression course (Fraguas, 2007; Rottenberg, 2005), the robustness and specificity of this finding are unclear. To provide a stronger test, RSA reactivity to three emotion films (happy, sad, fear) and to a more robust stressor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 59 publications
3
27
0
Order By: Relevance
“…Although evaluating depression on a dimensional level may improve potential power to detect nuanced effects and is consistent with evidence supporting the dimensional structure of depression (e.g., Liu, 2016), the clinical significance of the present results is not immediately clear (although results with RSA reactivity in clinical samples have paralleled those in the present study; e.g., Fraguas et al, 2007; Panaite et al, 2016; Rottenberg, Kasch, Gross, & Gotlib, 2002; Rottenberg, Salomon, Gross, & Gotlib, 2005). Future studies also should consider evaluating depression severity and perseverative cognition using interviewer-based methods that may be less susceptible to reporter bias than self-report scales.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Although evaluating depression on a dimensional level may improve potential power to detect nuanced effects and is consistent with evidence supporting the dimensional structure of depression (e.g., Liu, 2016), the clinical significance of the present results is not immediately clear (although results with RSA reactivity in clinical samples have paralleled those in the present study; e.g., Fraguas et al, 2007; Panaite et al, 2016; Rottenberg, Kasch, Gross, & Gotlib, 2002; Rottenberg, Salomon, Gross, & Gotlib, 2005). Future studies also should consider evaluating depression severity and perseverative cognition using interviewer-based methods that may be less susceptible to reporter bias than self-report scales.…”
Section: Discussionsupporting
confidence: 72%
“…However, recent work has suggested that RSA reactivity (vagal withdrawal) in response to sadness might be an index of regulatory flexibility that is particularly relevant to understanding depression and depression risk (for recent reviews, see Hamilton & Alloy, 2016; Stange et al, in press). Indeed, MDD appears to be characterized by a lack of RSA reactivity in response to sadness (Bylsma et al, 2014; Rottenberg, Clift, Bolden, & Salomon, 2007a), and individuals who have lower RSA reactivity (or vagal withdrawal) may be at risk for the onset of symptoms of depression and a poorer course of MDD (Panaite et al, 2016; Rottenberg et al, 2005; Stange et al, 2017). However, few such prospective studies have been conducted to evaluate the extent to which low RSA reactivity confers risk for future depression.…”
mentioning
confidence: 99%
“…The most commonly used situation was one in which participants defended themselves from an offense, such as being wrongly accused of theft or defending themselves against a traffic ticket (Ahrens et al, 2008; Bylsma et al, 2014; Cyranowski, Hofkens, Swartz, Salomon, & Gianaros, 2011; Hughes & Stoney, 2000; Panaite et al, 2016; Rottenberg et al, 2007). Another study included role-playing tasks, such as providing negative feedback to an employee and an unscripted debate on abortion (Gordon et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Most film clips were a sadness-induction (Rottenberg, Wilhelm, Gross, & Gotlib, 2003), usually a clip from “The Champ” in which a boy is grieving over the death of his father (Panaite et al, 2016; Pang & Beauchaine, 2013; Rottenberg, Salomon, Gross, & Gotlib, 2005; Yaroslavsky, Bylsma, Rottenberg, & Kovacs, 2013a; Yaroslavsky, Rottenberg, & Kovacs, 2013b, Yaroslavsky, Rottenberg, & Kovacs, 2014). For children, sadness-inducing film clips included the scene from “The Lion King” when the young lion is in the stampede (Gentzler, Santucci, Kovacs, & Fox, 2009; Yaroslavsky et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation